Do liberal blood transfusions cause more harm than good? - Goodnough, LT; Murphy, M (2014)
Guidelines and evidence from randomised controlled trials and meta-analyses increasingly support restrictive blood transfusion, but it is being implemented only slowly, explain LAWRENCE TIM GOODNOUGH: and MICHAEL MURPHY: . They argue that electronic systems for clinical decision support could improve blood use.